Nomenclature and definition in asymmetric regional body overgrowth. Issue 7 (5th May 2017) - Kalish, Jennifer M.; Biesecker, Leslie G.; Brioude, Frederic; Deardorff, Matthew A.; Di Cesare‐Merlone, Alessandra; Druley, Todd; Ferrero, Giovanni B.; Lapunzina, Pablo; Larizza, Lidia; Maas, Saskia; Macchiaiolo, Marina; Maher, Eamonn R.; et al.
Abstract : We designate a novel term "isolated lateralized overgrowth" (ILO) for the findings previously described as "isolated hemihypertrophy" and "isolated hemihyperplasia." ILO is defined as lateralized overgrowth in the absence of a recognized pattern of malformations, dysplasia, or morphologic variants. ILO is likely genetically heterogeneous. Further study is required to determine more of the underlying genetic etiologies and potential associations with currently unrecognized patterns of malformation.